2017
DOI: 10.1515/pjvs-2017-0055
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Study of Canine Mast Cell Tumours According to the Histological Malignancy Grade

Abstract: The aim of the study was to identify significant relationships between the tumour malignancy grade and dogs' age, breed, sex, size, and location of mast cell tumours (MCTs). MCTs accounted for 13.27% of all diagnosed canine skin tumours. The highest incidence was recorded among Boxers, Labrador Retrievers, American Staffordshire Terriers, and Golden Retrievers. Statistical analysis revealed significantly higher probability of occurrence of the grade I mast cell tumour in the French Bulldog in the head, neck, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
3
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 31 publications
5
18
3
1
Order By: Relevance
“…Boxers have previously been reported to have decreased odds of high‐grade MCTs by Mochizuki et al, which was not replicated by our findings. Increased odds of MCTs being histologically high grade have previously been reported in Shar Peis in Poland by Smiech et al (2017), which is consistent with our findings from our Australian population . Breeds that were reported to have increased odds of high‐grade MCTs by Mochizuki et al included Beagles, Bulldogs, Cocker Spaniels, Poodles, Shih Tzus and Rottweilers.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Boxers have previously been reported to have decreased odds of high‐grade MCTs by Mochizuki et al, which was not replicated by our findings. Increased odds of MCTs being histologically high grade have previously been reported in Shar Peis in Poland by Smiech et al (2017), which is consistent with our findings from our Australian population . Breeds that were reported to have increased odds of high‐grade MCTs by Mochizuki et al included Beagles, Bulldogs, Cocker Spaniels, Poodles, Shih Tzus and Rottweilers.…”
Section: Discussionsupporting
confidence: 92%
“…Various breed predilections to develop MCTs have been well explored previously, identifying dogs of Bulldog origin in particular to have an increased risk of MCT development . However, as this study identified various breeds displaying increased or decreased risk of a MCT being of high histological grade, it is likely that the genes responsible for MCT development differ from those that influence malignancy.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations